Health as a right and axis of protests in posadas, misiones, argentina - Miguel Alejandro Avalos (Cuaderno Urbano, 2020)
Posadas is a city that has experienced a significant increase in its levels of poverty and indigence in recent years, increasing on the one hand the number of informal settlements and, on the other, the demographic density of existing ones. This has led to an increasing number of families living in precarious conditions, exposed to various illness and suffering from numerous ailments. In this work we analyze the speeches made in different local media, between the months of January and December 2017, by people living in informal settlements in the city who participated in different mobilizations. In them we see how the incidence of different pathologies associated with poor living conditions was exposed and “staged” in different actions of social protest, through which they managed to install their demands towards the State (health, land, work, housing, among others).